Social Responsibility in the Sphere of Tourism in Kazakhstan - NIKIFOROVA, Nina; SMYKOVA, Madina; MUTALIYEVA, Lyailya; MUSSINA, Kamshat (Journal of Environmental Management and Tourism, 2019)
The rapid development of the tourism market has led to the fact that it does not always function within the framework of social responsibility. The current research was conducted to identify the level of social and corporate responsibility of participants in the tourist market. The studies revealed a low level of responsibility between tour operators and travel agents, which is manifested in the unfair work of tourist organizations, and their failure to duly fulfill obligations to partners. In addition, a stable social responsibility system has not been formed and tour operators and travel agents are not always honest and comply with the terms of the contract. The tourist market functions effectively if the relationship between all its participants is ensured and each of them is responsible for the results of its activities to partners and tourists. Therefore, the issues of creating such regulatory mechanisms in this sector become relevant, when social and corporate responsibility are secured not only by legal documents but are also the most important condition for their activities for all market participants. In this regard, the article provides recommendations aimed at addressing problems related to increasing the social responsibility of participants in the tourist market.